Rancang Bangun Sistem Pakar Diagnosis Gangguan Preferensi Seksual Menggunakan Metode Certainty Factor pada Institusi Kepolisian - Syafi'i, Imam; Jusak, Jusak; Sutomo, Erwin (Jurnal Sistem Informasi dan Komputerisasi Akuntansi (JSIKA), 2014)
A sexual preference disorder or Paraphilia is a deviate act that is hidden by the subject. It appears to be ignoring or hurting other people. Currently, Police institutions have implemented ways to know about this sexual abnormality. However, in the identification process there are similar symptoms that leads to the same conclution of the specific kind of paraphilia. In this case, it can cause a mistake in determining the type of sexual preference disorder along with the limitation to psychology staff and time limitation also made the solution to the case to be delayed. Based on the problems above, then the expert system is made that can help part of the psychology especially to those who do not have a clinical background to diagnose this sexual preference disorder to expedite the process of the psychological test and not to delay the settlement of the case. The certainty factor expert system will identify every symptom that is experienced by the problematic person, and the system will produce a diagnosis of sexual preference disorder result towards the problematic person. The trial result of the expert system application shows that the system is capable to identify the type of the disturbance in sexual preference with the accuracy of 93, 3%. The following result is made based on the input that is given by the user and compared with the diagnose result that is been done by police expert clinical psychology in the amount of 15 cases.